Pneumothorax necessitans in a patient with trapped lung and rheumatoid arthritis. (25th April 2013) - Ahmed, Rumman; Ahmed, Usama; Syed, Imran
Abstract : The authors report the case of a patient with a background of trapped lung following thoracocentesis who developed an anterolateral intercostal pneumothoracocele resulting in a pneumothorax necessitans (PN). Our purpose is to highlight the pathophysiology and interesting radiological features associated with PN in trapped lung. Our case is particularly unique due to the subacute nature of its presentation in a patient with rheumatoid arthritis and unusual pre-existing lung pathology.